Aproximación crítica a la historiografía de San Isidoro de León - García Martínez, Aida (Estudios Humanísticos. Historia, 2005)
A pesar de ser la Iglesia de San Isidoro de León uno de los monumentos mejor documentados de la Edad Media española carece todavía hoy de un estudio monográfico exhaustivo. En este trabajo nos proponemos realizar un estado de la cuestión de las distintas interpretaciones que de él se han venido publicando desde el siglo XIX hasta hoy. ABSTRACT: In spite of the fact that San Isidoro de León church is one of the best documented monuments of the Spanish Middle Ages and being an extense bibliography available, there isn´t any monographic study which could clarify the doubts which it arouses. In this article we undertake the study on its famous and outstanding pantheon; our goal is to present a brief research of the different interpretations of the material which has been publishes since the XIXth century.